Membrane lipid biosynthesis in Acholeplasma laidlawii B: de novo biosynthesis of saturated fatty acids by growing cells. - Saito, Y (1977)
The de novo biosynthesis of fatty acids of 12 to 18 carbons from precursors of 5 carbons or fewer has been demonstrated in Acholeplasma laidlawii B. Radiolabeling experiments indicated that the normal primers for the synthesis of the even- and odd-chain fatty acids are acetate and propionate or valerate, respectively. Saturated straight-chain monomethyl-branched fatty acids of up to five carbons were readily utilized as primers, wheras more highly branched species and those possessing halogen substituents or unsaturation were not utilized. At primer concentrations of 1 to 3 mM, up to 80% of the total cellular lipid fatty acids were derived from exogenous primer. The mean chain length of the exogenous primer-derived fatty acids rose with increasing primer incorporation for methyl-branched short-chain fatty acids but was invariant for propionate. The products of de novo biosynthesis varied only slightly with temperature or cholesterol supplementation, suggesting that de novo biosynthesis is not directly influenced by membrane fluidity. Cerulenin inhibited de novo biosynthesis in a fashion that suggests the presence of two beta-ketoacyl thioester synthetases, which differ in substrate chain length specificity and in susceptibility to inhibition by the antibiotic.